Case study: Impact analysis of educational Chatbot use in supporting students in the online learning process - Afriani, Febi; Suyato, Suyato; Devi, Indra; Syafitri, Aisyah; Harahap, Nur Indri Yani; Simbolon, Ali Mustopa Yakub (Jurnal Inovasi Teknologi Pendidikan, 2024)
This research aims to analyze the impact of using educational chatbots in supporting students in online learning processes. The research methodology adopts a qualitative approach with a case study design to examine the effects of chatbot usage on students in online learning. Data collection techniques involve conducting in-depth interviews with students, teachers, and school administrators, engaging in participatory observation during online learning sessions, and analyzing official documents and chatbot interaction logs. The research findings indicate that the use of chatbots significantly enhances student engagement, facilitates quick access to information, and provides personalized support in understanding the material. Furthermore, chatbots successfully create an interactive and responsive learning environment, boosting students' learning motivation and problem-solving abilities. The primary conclusion drawn from this research is that educational chatbots have a positive impact on improving the effectiveness of online learning by strengthening the interaction between students and the learning platform. The implementation of chatbots can be an effective solution to enhance the efficiency and quality of student's learning experiences in virtual environments. These findings offer valuable insights for further development in integrating chatbot technology into the context of online education, with the potential to improve accessibility, effectiveness, and holistic student experiences in distance learning.